A Gamma Alarm system for radiation protection - René Toledo Acosta; Guillermo Mesa Pérez; Dania Soguero González; Sandra Fernández Yanes; Bárbaro Robaina Martínez; Eduardo Valdés-Balsinde Fraga (Nucleus, 2017)
This paper describes the development of an instrument for radiological monitoring, identified as Gamma Alarm (GAMAL01). The instrument monitors the increment of radiation count rate and produces an alarm signal, when the count rate becomes superior to a fixed threshold value. The threshold is fixed to assure that the signal emission will start when the value of the radiation count rate may cause a non acceptable radiological exposition of the personnel, according to the radiological safety regulations existing in the country. Following the signal the personnel must be evacuated from the affected place. The instrument consists of two sections, an analogical section and a digital one.